Alternative flotation methods, adverse selection, and ownership structure: evidence from seasoned equity issuance in the U.K. - Slovin, M.B; Sushka, M.E; Lai, K.W.L (Journal of Financial Economics, 2000)
We examine valuation effects of announcements of seasoned equity issuance and assess the impact of the choice of flotation method in the U.K. Rights offerings are predominant, but in 1986, British firms gained the flexibility to conduct placings, which are comparable to U.S. firm commitment offerings. A placing is a fixed-price bought deal that increases ownership dispersion. Placings generate significantly positive share price effects, whereas rights offerings have large negative valuation effects that become more adverse after 1985. We conclude that the option to conduct placings enhances the ability of firms to signal their quality and to use a seasoned equity offering to reduce ownership concentration.